The mediation effect of vitamin A and vitamin D supplement in the association between serum vitamin K levels and musculoskeletal disorders in preschool children - Ge, Qiaoyue; Zhang, Lu; Sun, Zeyuan; Cai, Jiarui; Jiang, Xia; Wang, Hong; Li, Xinxi; Yu, Chuan; Xiao, Chenghan; Liu, Zhenmi (Frontiers in Nutrition, 2023)
Introduction Vitamin K deficiency may elevate the incidence of musculoskeletal disorders (MSD), whereas it lacks validation for pediatric populations and has uncertain dose recommendations. In this context, we hypothesized that serum vitamin K levels are associated with MSD in preschool children, and the widely used vitamin A and vitamin D supplements may mediate these associations based on potential mechanisms, which expects to provide guidance for future practice. Methods A cross-sectional study was conducted in Sichuan province in southwestern China, from January 2021 to May 2022. Serum levels of vitamin K1/K2 and 25(OH)D were determined using the high-performance liquid chromatography method, and the diagnosis of MSD was executed by clinicians. Overall and stratified logistic regression analysis based on categorized 25(OH)D levels were conducted to assess association between serum vitamin K levels and MSD prevalence after adjusting for confounders. Mediation analysis was further performed and vitamin A and D supplementation was regressed as the mediator. Results A total of 6,368 children aged 0–6 years old were enrolled. MSD was identified in 1179 (18.51%) of the children, while 5,189 (81.49%) of them did not present such disorder. After adjusting confounders, a significant difference was found in serum vitamin K1 level between children in MSD and Non-MSD group (OR = 0.802, 95%CI 0.745–0.864). No significant difference was found in serum vitamin K2 level between the two groups (OR = 0.975, 95%CI 0.753–1.261). The association between vitamin K1 level and MSD prevalence was partly (36.8%) mediated by vitamin A and D supplementation. Conclusions A low serum vitamin K1 level is connected with an increased risk of MSD among children, highlighting that vitamin A and D supplementation is a helpful intervention to prevent MSD in children with vitamin K deficiency.